2014
DOI: 10.1002/anie.201402834
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Synthesis of 8‐Oxabicyclooctanes by Intermolecular [5+2] Pyrylium Cycloadditions

Abstract: Highly enantioselective intermolecular [5+2] cycloadditions of pyrylium ion intermediates with electron-rich alkenes are promoted by a dual catalyst system composed of an achiral thiourea and a chiral primary aminothiourea. The observed enantioselectivity is highly dependent on the substitution pattern of the 5π component, and the basis for this effect is analyzed using experimental and computational evidence. The resultant 8-oxabicyclo[3.2.1]octane derivatives possess a scaffold common in natural products and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…90 The author observed that a small amount of water is essential for obtaining high ee's of the products -the use of Na 2 CO 3 ·H 2 O and Na 2 CO 3 provided the products in 88% and 32% ee's, respectively. This 93 It was found that the replacements of -H by -Me group in R 2 enhanced the ee's from 47% to 90% suggesting its critical role in controlling the enantio-determining transition state i.e. 364 whose formation was confirmed by mass spectroscopic analysis.…”
Section: Organic and Biomolecular Chemistry Accepted Manuscriptmentioning
confidence: 81%
“…90 The author observed that a small amount of water is essential for obtaining high ee's of the products -the use of Na 2 CO 3 ·H 2 O and Na 2 CO 3 provided the products in 88% and 32% ee's, respectively. This 93 It was found that the replacements of -H by -Me group in R 2 enhanced the ee's from 47% to 90% suggesting its critical role in controlling the enantio-determining transition state i.e. 364 whose formation was confirmed by mass spectroscopic analysis.…”
Section: Organic and Biomolecular Chemistry Accepted Manuscriptmentioning
confidence: 81%
“…Significant advances in enantioselective additions to cyclic oxocarbenium ions have been made by using organo- and/or Lewis acid catalysts to deliver a number of different carbon nucleophiles. [8] We have developed a copper(I)-catalyzed method to enable enantioselective alkynylation via addition of a chiral organometallic nucleophile. [9] However, the vast majority of enantioselective additions of carbon nucleophiles are limited to the formation of tertiary stereocenters via additions to oxocarbenium ions with sterically and electronically distinct substituents on the cationic carbon (C vs. H, Scheme 1A).…”
mentioning
confidence: 99%
“…[10] Only a single method exists for the formation of tetrasubstituted stereocenters via enantioselective addition to oxocarbenium ions; Jacobsen's thiourea-catalyzed [5+2] cycloaddition of pyrilium ions enables formation of α-trialkyl tetrasubstituted stereocenters on 8-oxabicylcooctanes (Scheme 1B). [8k, 8l] Beyond this, there are no examples of setting tetrasubstituted stereocenters via additions of carbon nucleophiles to oxocarbenium ions, and no such additions enable formation of challenging diaryl tetrasubstituted stereocenters. We now report the first enantioselective addition to oxocarbenium ions to provide α-diaryl tetrasubstituted stereocenters.…”
mentioning
confidence: 99%
“…6 The Jacobsen group has now also demonstrated that chiral thiourea catalysts can also control enantioselectivity in both intra- and intermolecular cyclizations of pyrilium ion intermediates. 7 Subsequently, Terada and Floreancig showed that phosphoric acid catalysts can also be used to catalytically generate chiral oxocarbenium ion electrophiles, which undergo enantioselective attack by hydride or allyl nucleophiles, respectively. 8 In a distinct strategy, Schaus has demonstrated the complementary approach of catalytic generation of a chiral nucleophile via tartarate-derived diol-catalysis of vinyl and aryl boronate esters.…”
Section: Introductionmentioning
confidence: 99%